(untitled) (Bangladesh Journal of Medical Physics, 2014)
Our extended group in Dhaka University has shown that frequency Distribution of F-Latency (DFL) of peripheral nerve trunks may be used for the detection of Cervical Spondylotic Neuropathy (CSN). A double blind study was performed recently to ascertain the efficacy of DFL in the detection of CSN using MRI findings as the benchmark, which was performed on 62 median nerves of 31 volunteers within an age range of 20 and 80 years. In our laboratory DFL is obtained by grouping F-latency data into 2ms bins and then plotting a frequency polygon. The shapes of the resulting polygons are sorted into two categories: i) single peak and ii) broad peak or multiple peaks. The first category was taken to represent normalcy while the second category was taken to represent CSN. The present work was taken up to study the effect on the polygon patterns due to shifting of the starting point of each bin by 1ms. Two decisions were made for each nerve regarding normalcy or CSN based on both the individual polygon patterns. Two more decisions were made based on the logic AND and logic OR operations of the above two decisions. These four individual decisions from all the nerves were then compared with MRI findings. This shows that such bin shifting and a decision based on OR logic on the two DFLs thus obtained gives the best overall efficacy compared to all the other procedures. DOI: http://dx.doi.org/10.3329/bjmp.v6i1.19762 Bangladesh Journal of Medical Physics Vol.6 No.1 2013 75-81